Design and implementation of proxy-protected proxy signature based on SM2 - Qing-xiao GUO; Da-wei ZHANG; Liang CHANG; Xiao-dong LIU; Jing-wen SONG (网络与信息安全学报)
Based on the SM2 digital signature standard,a proxy-protected proxy signature scheme was designed.Through the design of the agent authorization mechanism,the protection of the proxy signer was realized.The proxy signature was realized by the proxy signer who represents the original signer through the improvement of the SM2 digital signature algorithm.The security analysis shows that the designed algorithm is verifiable,identifiable,distinguishable,non-repudiation,and strong unforgeability.Finally,the program was implemented using the C language and the Polarssl library,and the performance was compared with the SM2 digital signature.The analysis shows that the algorithm has good usability in performance.